Penanaman Nilai Karakter kepada Siswa melalui Media Visual Banner di SMP Islam Sabilal Muhtadin Banjarmasin - Jamiatul Hamidah; Akhmad Syakir (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
Every educational institution longs for the formation of the noble character of students which is the ultimate goal in education. This noble character can be formed through learning activities in the classroom as well as learning outside the classroom. Cultivating culture or good habits in students can be done through the media banners posted in the school environment such as in classrooms, libraries, school hallways, and laboratories. For this reason, this study aims to describe the cultivation of character values ​​through the visual banner media at SMP Islam Sabilal Muhtadin Banjarmasin. The research method used is descriptive qualitative method with text analysis approach, because the data comes from the interpretation of the pamphlets or banners posted in the halls of the Islamic Junior High School Sabilal Muhtadin Banjarmasin. The data was collected by documenting the banner through photos which were then identified and classified based on the type of sentence contained in the banner. Data validation was carried out by interviewing the school. The documented number of banners was 12. After the data is classified, then it is described so that conclusions can be drawn. The results showed that the visual media of banners or banners can be used as a medium to instill values ​​of religious character, discipline, care for the environment, and love of science. Media banners are made using formal language, English, and everyday language that is easily understood by students. The content of the sentence in the banner is usually in the form of a sentence containing motivation, reminders, invitations, and prohibitions.